Understanding Household’s Travel Costs Budget Frontier in Banda Aceh, Indonesia - Sugiarto Sugiarto; Lulusi; Muhammad Isya; Fadhlullah Apriandy; Fuadh Ramadhan (Communications - Scientific letters of the University of Zilina, 2021)
This study aims to explore the constraints of the Travel Costs Budget Frontier (TCBF) before a full-charged fare is implemented for the bus system known as the “Trans Koetaradja” in the city of Banda Aceh, Indonesia. A stochastic frontier analysis was used to identify how people allocate their share of income for transportation in line with their mobility and socio-demographic characteristics. The findings showed the TCBF to be influenced by commuting trip activities, private mode usage, owning car and motorcycle and income limits. Barriers were observed to be restricting the low-medium income groups. Owning their own private modes within the low-medium income groups does mean household disbursement and could impose their transport expenditure rather than public modes usage. There is a need to devise policies considering the low-medium incomes to implement impartial full-charge to ensure affordable bus fare.